Synthesis and Photophysical and Electrochemical Properties of Functionalized Mono-, Bis-, and Trisanthracenyl Bridged Ru(II) Bis(2, 2′:6′, 2″-terpyridine) Charge Transfer Complexes. (30th April 2014) - Adeloye, Adewale O.; Ajibade, Peter A.
Abstract : With the aim of developing new molecular devices having long-range electron transfer in artificial systems and as photosensitizers, a series of homoleptic ruthenium(II) bisterpyridine complexes bearing one to three anthracenyl units sandwiched between terpyridine and 2-methyl-2-butenoic acid group are synthesized and characterized. The complexes formulated as bis-4 ′ -(9-monoanthracenyl-10-(2-methyl-2-butenoic acid) terpyridyl) ruthenium(II) bis(hexafluorophosphate) (RBT1 ), bis-4 ′ -(9-dianthracenyl-10-(2-methyl-2-butenoic acid) terpyridyl) ruthenium(II) bis(hexafluorophosphate) (RBT2 ), and bis-4 ′ -(9-trianthracenyl-10-(2-methyl-2-butenoic acid) terpyridyl) ruthenium(II) bis(hexafluorophosphate) (RBT3 ) were characterized by elemental analysis, FT-IR, UV-Vis, photoluminescence, 1 H and 13 C NMR spectroscopy, and electrochemical techniques by elemental analysis, FT-IR, UV-Vis, photoluminescence, 1 H and 13 C NMR spectroscopy, and electrochemical techniques. The cyclic voltammograms (CVs) of (RBT1 ), (RBT2 ), and (RBT3 ) display reversible one-electron oxidation processes at E 1 / 2 = 1.13 V, 0.71 V, and 0.99 V, respectively (versus Ag/AgCl). Based on a general linear correlation between increase in the length of π -conjugation bond and the molar extinction coefficients, the Ru(II) bisterpyridyl complexes show characteristic broad and intense metal-to-ligand charge transfer (MLCT) band absorption transitions between 480–600 nm, ε = 9.45 × 10 3  M −1  cm −1, and appreciable photoluminescence spanning the visible region.